Fetal Skeletal Lethal Dysplasia: Case Report Displasia Esquelética Letal Fetal: Relato de Caso - Alexandre Mello Savoldi; Maria Auxiliadora Monteiro Villar; Heloisa Novaes Machado; Juan C. Llerena Júnior (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract The clinical management and decision-making in pregnancies in which there is suspicion of lethal fetal malformations during the prenatal period, such as lethal skeletal dysplasia (SD), demand a multidisciplinary approach coordinated by an experienced physician. Based on the presentation of a case of osteogenesis imperfecta type IIA, we offer and discuss recommendations with the intention of organizing clinical and laboratory investigations aiming toward the clinical management, prognosis, and etiological diagnosis of these malformations, as well as genetic counselling to patients who wish to become pregnant.